2019
DOI: 10.1093/sleep/zsz207
|View full text |Cite
|
Sign up to set email alerts
|

An attempt to identify reproducible high-density EEG markers of PTSD during sleep

Abstract: Study Objectives We examined electroencephalogram (EEG) spectral power to study abnormalities in regional brain activity in post-traumatic stress disorder (PTSD) during sleep. We aimed to identify sleep EEG markers of PTSD that were reproducible across nights and subsamples of our study population. Methods Seventy-eight combat-exposed veteran men with (n = 31) and without (n = 47) PTSD completed two consecutive nights of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 59 publications
7
36
0
Order By: Relevance
“…Both reduced and increased delta power activity during NREMS have been reported in PTSD patients (Woodward et al, 2000;Germain et al, 2006;Insana et al, 2012;de Boer et al, 2020;Wang et al, 2020). Thus, the SPS mouse model may recapitulate the symptoms of the subset of PTSD patients showing reduced NREMS delta power (Woodward et al, 2000;de Boer et al, 2020;Wang et al, 2020). In our study, we found that chemogenetic inhibition of the mFPC activity could specifically reverse the SPSinduced acute suppression of delta power during NREMS and most of the long-term sleep/wake EEG abnormalities.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Both reduced and increased delta power activity during NREMS have been reported in PTSD patients (Woodward et al, 2000;Germain et al, 2006;Insana et al, 2012;de Boer et al, 2020;Wang et al, 2020). Thus, the SPS mouse model may recapitulate the symptoms of the subset of PTSD patients showing reduced NREMS delta power (Woodward et al, 2000;de Boer et al, 2020;Wang et al, 2020). In our study, we found that chemogenetic inhibition of the mFPC activity could specifically reverse the SPSinduced acute suppression of delta power during NREMS and most of the long-term sleep/wake EEG abnormalities.…”
Section: Discussionsupporting
confidence: 66%
“…However, future studies are needed to investigate the precise roles of different types of mPFC neurons in the SPS-induced sleep-wake EEG disturbances as the chemogenetic inhibition approach in our study result in the inhibition of all neuronal populations. Both reduced and increased delta power activity during NREMS have been reported in PTSD patients (Woodward et al, 2000;Germain et al, 2006;Insana et al, 2012;de Boer et al, 2020;Wang et al, 2020). Thus, the SPS mouse model may recapitulate the symptoms of the subset of PTSD patients showing reduced NREMS delta power (Woodward et al, 2000;de Boer et al, 2020;Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The sample used in the present study was the same as that used in our previous work, in which we reported the clinical characteristics and sleep architecture parameters of the participants ( Laxminarayan et al, 2020 , Wang et al, 2020a , Wang et al, 2020b ). Briefly, PTSD and non-PTSD participants did not differ significantly with respect to age or the Apnea-Hypopnea Index (AHI) in both the discovery and replication sets ( p > 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…The lack of reliable sleep markers of PTSD presents an obstacle to understanding the pathophysiology of its associated sleep symptoms and to developing sleep-specific diagnostics and interventions for the disorder. To bridge this gap, we have made several attempts to identify brain activity changes in PTSD during sleep that are reproducible, by examining features of electroencephalogram (EEG) spectral power ( Wang et al, 2020a ), EEG synchrony ( Laxminarayan et al, 2020 ), and sleep spindles ( Wang et al, 2020b ). In particular, sleep spindles are signature neural events during non-rapid eye movement (NREM) sleep that are thought to play key roles in sleep-dependent memory consolidation ( Fogel and Smith, 2011 ) and sleep protection ( Astori et al, 2013 , Luthi, 2014 ).…”
Section: Introductionmentioning
confidence: 99%